The role of technology in the water–energy–food nexus. A case study: Kerinthos, North Euboea, Greece - Sargentis, G.-Fivos; Mamassis, Nikos; Kitsou, Olga; Koutsoyiannis, Demetris (Frontiers in Water, 2024)
The water–energy–food (WEF) nexus is a basic element of prosperity, yet it is not equally distributed on the land. Human progress has optimized the function of the WEF nexus to bridge the inequality gap. In order to understand this progress, this study compares the preindustrial and modern agricultural practices in an area in Greece. Interviews were conducted with an elderly man who lived in the 1950s, and the process was quantified in units of WEF. The same procedure was also carried out with modern farmers for modern agricultural practices. In comparing the past and present agricultural processes, it is observed that today, a farmer can feed approximately 100 times more people. This feat has been achieved as modern practices push the land with energy sources in multiple ways (fuels and fertilizers). However, energy indices such as energy ratio, net energy gain, specific energy, and energy productivity do not seem to be improved. Furthermore, farmers prefer to pump underground water for irrigation, instead of utilizing the nearby river, as was done in the past when the river provided both energy to the watermill and an abundance of water for irrigation. In addition, as the price of wheat is dependent on the stock market, even in 2023, there are risks to food security, the cultivation of wheat was not economically efficient for farmers in this area in 2023.